Avaliação do sono em indivíduos com lipodistrofia generalizada congênita - Silva, Carla Pequeno (2017)
Introduction: Sleep is a cyclical and reversible functional state, essential to life. Sleep disorders affect approximately 45% of the world's population, a major global public health problem. Sleep disorders have the potential to encourage the onset of metabolic problems. In contrast, abnormality in metabolism has been associated with predictive causes of sleep disorders. The main risk factors for individuals with metabolic problems developing sleep abnormalities are related to glycemic control, duration of illness and obesity. These observations make generalized congenital lipodystrophy an interesting biological model for the study of mechanisms potentially associated with the development of sleep disorders, since, although rare, this disease has been referred to as a human metabolic model of ectopic fat, a condition present in obese and repercussions on metabolism. General objective: To describe sleep pattern characteristics of individuals with generalized congenital lipodystrophy. Specific objectives: To evaluate the subjective quality of sleep; To analyze the levels of sleepy daytime sleepiness; Assess the presence of sleep-disordered breathing. Methods: Transversal study of descriptive nature and quantitative approach. The research was developed at the Endocrinology Service Ambulatory of the Walter Cantídio University Hospital (HUWC). He made use of the Pittsburgh Sleep Quality Index (PSQI), Epwoth Sleepiness Scale (ESE) and polysomnography (PSG). The variables were described by median (minimum, maximum), mean. Results: Eight patients, aged between seven and 33 years, participated in the study. All patients presented poor sleep quality (IQSP global> 5) and excessive daytime sleepiness was present in two participants (ESS ≥ 10). The polysomnographic examination identified: Obstructive sleep apnea syndrome (OSAS) in (6/8) cases. Conclusions: All patients had abnormalities in sleep, diagnosis of OSAS in the majority of the individuals and precocity of problems related to sleep in young individuals.